2020
DOI: 10.3390/polym12061328
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Reclamation of Chitin and Protein-Containing Marine By-Products for the Production of Prodigiosin and the Evaluation of Its Bioactivities

Abstract: Chitin and protein-containing marine by-products (CPCMBPs), including crab shells, squid pens, and shrimp shells, were investigated as the sole carbon/nitrogen (C/N) source for prodigiosin (PG) production by Serratia marcescens TNU01 in a 250 mL Erlenmeyer flask and a 10 L bioreactor system. Among the used C/N source of CPCMBPs, squid pens powder (SPP) showed the most optimum PG productivity. Different ratios of chitin/protein combination were also used as the C/N sources for PG production. With a similar chit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(69 citation statements)
references
References 52 publications
6
63
0
Order By: Relevance
“…Our previous studies revealed that the salt composition, including sulfate and phosphate salts, demonstrate a significant effect on PG production using S. marcescens [11,[30][31][32] (Figure 3).…”
Section: The Effect Of Salt Composition and Some Parameters Of Fermenmentioning
confidence: 92%
See 4 more Smart Citations
“…Our previous studies revealed that the salt composition, including sulfate and phosphate salts, demonstrate a significant effect on PG production using S. marcescens [11,[30][31][32] (Figure 3).…”
Section: The Effect Of Salt Composition and Some Parameters Of Fermenmentioning
confidence: 92%
“…A review of the recent literatures found that numerous studies have reported on PG production. However, in most previous studies, PG production was conducted in a minor scale (in flasks) using commercial nutrients as C/N sources for fermentation [11]. Different to previous research, our study successfully engaged in cost-effective PG production at a large scale (a 15 L bioreactor system) using low-cost material (crab waste) as the C/N source for fermentation.…”
Section: The Effect Of Salt Composition and Some Parameters Of Fermenmentioning
confidence: 99%
See 3 more Smart Citations